A New Monocular Pose Estimation Method for the Coplanar P4P Problem - Xudong Yu; Yang Shang (Applied Sciences, 2022)
The Perspective of N Points (PNP) problem in optical measurement and machine vision is to estimate the pose parameters of an object by a monocular image. For traditional coplanar P4P methods, the four points must have known coordinates or be a rectangle’s four vertices. In this paper, a new method of the P4P problem for parallelogram objects without shape parameters is proposed to solve the objects’ pose and shape parameters based on the parallelogram vertices’ relative coordinate constraints. The correctness and effectiveness of the method have been verified through experiments. In addition to being used to estimate a parallelogram object’s pose and shape, the new method extends the conclusions of the coplanar P4P problem when the four points are a parallelogram’s four vertices.